Kreativitas matematis mahasiswa bertipe kepribadian ekstrovert-introvert dalam menyelesaikan masalah geometri - Izzah, Nuurul; As’ari, Abdur Rahman; Sisworo, Sisworo (Jurnal Kajian Pembelajaran Matematika, 2022)
This study aims to analyze the mathematical creativity of college students with extrovert-introvert personality types based on creativity indikators in solving geometry problems. The research approach and design uses a quantitative approach with cross sectional design. The research subject were 67 college students of state University of Malang in Mathematics Department semester 2, 4, and 6. Data collection techniques using questionnaires and tests. The results showed that: (1) the college students ability of extroverted personality type to produce diverse solutions (fluency) and generate diverse ideas (flexibility) increased in semester 2, 4, and 6. Meanwhile, all college students in semester 2, 4, and 6 not produce new solutions or ideas (novelty). (2) the college students ability of introverted personality type to produce diverse solutions (fluency) decreases in semester 6. The college students ability to generate diverse ideas (flexibility) increases in semester 2, 4, and 6. Meanwhile, the college students ability to produce new solutions or ideas (novelty) increases in semester 6.